THE INFLUENCE OF THE PERFORATION DENSITY AND DAMAGED ZONE PERMEABILITY ON A GAS WELL PRODUCTION - Alexandra Catalina Damascan; Mihai Albulescu; Doru Stoianovici (Romanian Journal of Petroleum & Gas Technology, 2022)
The exploitation of wellbore condensate deposits must be carried out in such a way that both water and condensate from the productive layer are not entrained during extraction. That is precisely why the article analyzes the effect of the density of perforations of the productive layer on the amount of extracted gas. The effect of the area affected by the drilling on the produced gas flow is also studied. After 50 years since the first use of the mechanical realization of the perforations of the productive layers of the gas wells, there is little data regarding the influence of the perforation geometry of a gas well, namely the way of communication between the production layer and the borehole, on its production. The aim of this paper is to simulate the operation of the well for different values specific to the drilling mode, highlighting its production. The problem is addressed by nodal analysis. The numerical simulators were used to simulate the flow of the mixture through the layer-well system and respectively through the mixture pipe.